2014
DOI: 10.3103/s0095452714050090
|View full text |Cite
|
Sign up to set email alerts
|

cyp11A1 Canola plants under short time heat stress conditions

Abstract: 11In order to investigate the high temperature tolerance of spring canola plants (Brassica napus L.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Carotenoids play two major roles in cyanobacteria: (a) serving as a light-harvesting pigment during photosynthesis and (b) providing protection against photodamage (Hirschberg and Chamovitz, 1994). Many reports have shown that the accumulation of carotenoids occurs under heat stress in order to protect the photosynthetic machinery against photooxidation (Sakhno et al, 2014). Heat stress has been shown to adversely affect phycocyanin; however, small heat shock proteins may provide protection against phycocyanin degradation (Nakamoto and Honma, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids play two major roles in cyanobacteria: (a) serving as a light-harvesting pigment during photosynthesis and (b) providing protection against photodamage (Hirschberg and Chamovitz, 1994). Many reports have shown that the accumulation of carotenoids occurs under heat stress in order to protect the photosynthetic machinery against photooxidation (Sakhno et al, 2014). Heat stress has been shown to adversely affect phycocyanin; however, small heat shock proteins may provide protection against phycocyanin degradation (Nakamoto and Honma, 2006).…”
Section: Discussionmentioning
confidence: 99%